Initial glaciological investigations on a large Himalayan glacier: Drang Drung (Zanskar, Ladakh, India) - Mohd. Farooq Azam; Md. Arif Hussain; Himanshu Kaushik; Smriti Srivastava; Manoj Kumar Munda; Arindan Mandal; Ishmohan Bahuguna; Sushil Kumar Singh; Mohd Jawad (Journal of Glaciology)
In situ glaciological observations in the Himalaya–Karakoram (HK) region mostly come from small glaciers. Drang Drung (69.6 km2, Zanskar, Ladakh) is the largest glacier in the HK monitored for in situ glacier-wide mass balances applying the traditional glaciological method. During 2021–23, point ablation varies from –1.8 to –8.3 meter water equivalent (m w.e. a–1) in the ablation area, and from 0.15 to 1.70 m w.e. a–1 in the accumulation area. The mean glacier-wide mass balance is −0.74 ± 0.43 m w.e. a−1 over 2021‒2023, corresponding to a mean equilibrium line altitude of 5134 m a.s.l. and accumulation area ratio of 0.53. The mean annual vertical mass-balance gradient of 0.62 m w.e. (100 m)–1 on Drang Drung Glacier resembles that observed on other Himalayan glaciers. These initial investigations on Drang Drung Glacier address the gap for glacier monitoring in the Zanskar Range and will be continued in the long term.